Jesus and the church : the foundation of the church in the New Testament and modern theology - Avis, Paul (London, T&T Clark, 2021)
"Did Jesus 'found' the Christian Church? If so, what then is Church's true foundation? Or does 'the Eucharist make the Church'? Paul Avis sets out his own answer to these questions. He argues that critical scholarship allows us to hold that there is something solid and dependable at the foundation of the Church's life and mission. The Church is battered and divided, but at its core is a treasure that is indestructible - the gospel of Christ, embodied in word and sacrament. Jesus did want a church in a sense, but not as we know it. Jesus himself proclaimed the gospel of the Kingdom and his disciples proclaimed the gospel whose content was Jesus Christ himself, the Kingdom in person. So a central theme of the book is the relationship between the Church and Christ, the Church and the gospel, the Church and the Kingdom. Jesus Christ, crucified and risen, is the sole foundation of the Church, but he cannot be without his people"--
Includes bibliographical references and index.
Keywords: Jesus Christ; Church